MUCOLYTICS FOR CHILDREN: DIFFICULT ISSUES, KEY SOLUTIONS - O. I. Simonova (Вопросы современной педиатрии, 2014)
The author analyzed the most common questions of mucolytic agents selection asked by clinicians. The various clinical effects of N-acetyl cysteine and indications for different forms of this drug, especially in infants, are discussed in the article. Indications and contraindications of acetyl cysteine usage for treatment of dry and productive cough in combination with other medicines in the first 24 hours of acute respiratory tract infections, accompanied by adherent bronchial discharge, are listed. The causes of the pulmonary«swamping» and measures of prevention of this condition are shown.